SUPPLY CHAIN MANAGEMENT COMPARISON OF NIKE AND ADIDAS SHOE PRODUCTION PRACTICES IN INDONESIA - Ansori, Dinar; Devi Septiana; Fadrian Gultom; Paulina Sandria Theresia Soegiarto; Denisa Ryan Angelita; Antyo Pracoyo (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Nike and Adidas products are two leading brands in the sports shoe industry that have a major impact on the global market. This research aims to find out the supply chain management of Nike and Adidas shoe production practices, as well as solutions to the challenges of each company's supply chain production practices. This research is classified as qualitative research using the library research method. The data analysis technique used by the author is carried out in various stages including through data collection, data display, data condensation, and carrying out conclusion drawing and verification. The results of this study indicate that: Supply chain management is an important aspect in the global manufacturing industry, and industry. The management of Nike's shoe production practices in Indonesia is that Nike works based on three principles of corporate organization, namely 1) Outsourcing; 2) Diversification, and 3) Corporate Social Responsibility. While the management of Adidas shoes production practices in Indonesia is based on: 1) Strategic Sourcing; 2) Demand Forecasting; 3) Product Customization; 4) Quality Control; 5) Distribution; and 6) Technology. The solution to sustainability challenges in the Adidas supply chain is to target the entire cycle in the management of social and environmental impacts, specifically related to water, chemicals, energy use, and labor rights. While Nike is more about: 1) New energy facilities; 2) Carbon emission reduction; 3) Diversion of Production Waste; 4) Recycle raw materials and 5) Reuse-A-Shoe and Nike Grind programs.